2017
DOI: 10.1038/s41598-017-02397-6
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I editing in human miRNAs is enriched in seed sequence, influenced by sequence contexts and significantly hypoedited in glioblastoma multiforme

Abstract: Editing in microRNAs, particularly in seed can significantly alter the choice of their target genes. We show that out of 13 different human tissues, different regions of brain showed higher adenosine to inosine (A-to-I) editing in mature miRNAs. These events were enriched in seed sequence (73.33%), which was not observed for cytosine to uracil (17.86%) editing. More than half of the edited miRNAs showed increased stability, 72.7% of which had ΔΔG values less than −6.0 Kcal/mole and for all of them the edited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…Like ADAR1, ADAR2 also can modulate microRNA processing. Since a number of micro RNAs like miR-1, miR-423 are associated with heart disease we thought of investigating the microRNA profile in ADAR2 knock out mouse heart (40). Surprisingly, we did not observe any up-regulated micro RNAs in the ADAR2 -/- mice heart.…”
Section: Discussionmentioning
confidence: 99%
“…Like ADAR1, ADAR2 also can modulate microRNA processing. Since a number of micro RNAs like miR-1, miR-423 are associated with heart disease we thought of investigating the microRNA profile in ADAR2 knock out mouse heart (40). Surprisingly, we did not observe any up-regulated micro RNAs in the ADAR2 -/- mice heart.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their secondary structure, A-to-I editing could occur in pri-, pre-and mature miRNAs, although the probability of editing events is likely dependent on the lengths of these different molecules [38,42,43] (Figure 3a). RNA cis-elements and the recruited ADAR isoform might also be important for miRNA editing, as highlighted by several studies, suggesting a preferred editing activity of nuclear ADARs, i.e., ADAR2 and ADAR1p110, depending on miRNA sequence characteristics [38].…”
Section: Adarmentioning
confidence: 99%
“…Consistent with the potential function of the hsa-miR-411 mutation in GBM, miR-411-5p is considered a brain-enriched miRNA and was previously associated with neurological and neuropsychiatric disorders 89,90 . Interestingly, miR-411-5p is posttranscriptionally modified (substitution A>I (inosine) in the 5th position of miR-411-5p seed) in both normal brain and glioblastoma multiforme tissues 87,91 . The precise function of this modification is not known; however, in vitro analyses revealed that pri-miRNA editing is likely to interfere with miRNA processing 92 .…”
Section: Hsa-mir-411mentioning
confidence: 99%